The Role of Music Teachers in Increasing Students' Interest in Learning - Lumban Tobing, Utama Paul Estomihi; Gulo, Jelia Oxfami; Nainggolan, Danris; Pasaribu, Andar Gunawan (Yayasan Bayt Shufiya Nusantara, 2025)
This study aims to analyze the role of music teachers in increasing students' interest in learning through the use of music media, both with technology and interactive methods in the learning process. The method used in this study is a literature study method, by collecting primary and secondary data from various sources, such as theses, books, articles, websites, and good practices applied by teachers in music learning. The results of the study show that the use of music media can create a fun learning atmosphere, which in turn can increase students' motivation and interest in learning. Music, with its ability to stimulate emotions and moods, has proven to be effective in motivating students to be more active and engaged in learning. Music teachers who are able to adapt learning approaches that are in accordance with technological developments and the needs of students can create a more interactive and productive learning environment. Therefore, integrating music as a tool in learning has great potential in improving the quality and effectiveness of learning as well as students' learning interests.